Escaping the Specters Within: Probing the Delineation of the Concepts of Dissociation, Formation of the Traumatic Bonds and Reenactment Aligning with Unresolved Trauma in Yanagihara’s A Little Life (Contemporary Journal of Social Science Review, 2024)
This study investigates the unending concept of dissociation, reenactment of trauma and formation of the traumatic bonds in the novel A Little Life by Hanya Yanagihara. The prime focus of this analysis is on the lives of four main characters of this novel, namely, Jude St. Francis, JB Marion, Willem Ragnarsson and Malcolm Irvine, who manifest the reenactment of trauma and possess fragmented identities because of the pain they endure because of their past experiences. All the four characters are indulged in self-loathing, self-harm and blame themselves for the experiences of their lives. There is a continuous cycle of their torture, and the flashbacks that haunt them. The research utilizes Judith Herman’s trauma theory as a guiding framework, portraying the implications of the trauma and how the characters reinforce their memories of traumatic instances as a form of defense mechanism for them. They also form bonds with their perpetrators in order to cope with the anguish and distress. Utilizing Herman’s trauma theory, the study reveals how unhealthy relationships are formed and how the characters are longing for the process of validation and social support. By detaching their memories and reenacting them, the study highlights how the individuals are able to gain control over their bodies through self-harm, which devastates their identity, psychological development and relationships.